Allelic Heterogeneity in the COH1 Gene Explains Clinical Variabilityin Cohen Syndrome - Hennies, Hans Christian (The American Society of Human Genetics, 2004)
Cohen syndrome is a rare autosomal recessive disorder with a variable clinical picture mainly characterized by developmental delay, mental retardation, microcephaly, typical facial dysmorphism, progressive pigmentary retinopathy, severe myopia, and intermittent neutropenia. A Cohen syndrome locus was mapped to chromosome 8q22 in Finnish patients, and, recently, mutations in the gene COH1 were reported in patients with Cohen syndrome from Finland and other parts of northern and western Europe. Here, we describe clinical and molecular findings in 20 patients with Cohen syndrome from 12 families, originating from Brazil, Germany, Lebanon, Oman, Poland, and Turkey. All patients were homozygous or compound heterozygous for mutations in COH1. We identified a total of 17 novel mutations, mostly resulting in premature termination codons. The clinical presentation was highly variable. Developmental delay of varying degree, early-onset myopia, joint laxity, and facial dysmorphism were the only features present in all patients; however, retinopathy at school age, microcephaly, and neutropenia are not requisite symptoms of Cohen syndrome. The identification of novel mutations in COH1 in an ethnically diverse group of patients demonstrates extensive allelic heterogeneity and explains the intriguing clinical variability in Cohen syndrome.